EMOTSIONAL INTELLEKT BO`LAJAK MUTAXASSISLARNING MUHIM XUSUSIYATI SIFATIDA - Rahmatullayeva Zamira Olimjonovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article discusses the specific features of emotional intelligence in future professionals, the role and importance of emotional intelligence in interpersonal relationships, professional success, and methods of its development. Key words: higher education, student, specialist, intelligence, emotional intelligence, educational process, professional activity, professional stress.